Propuesta de ruta agroturística de las Parroquias Vilcabamba, Yangana y Quinara del Cantón Loja, provincia de Loja - CUEVA ABAD, JORGE ANDRÉS (2018)
Ecuador is a special country that has one of the greatest biodiversities in the world in flora and fauna, besides having an innumerable list of indigenous ethnic groups, with their customs and religions, each of these attractive for its process and respect. The southern region of Ecuador and especially the province of Loja, also known as the musical and cultural capital of Ecuador, has countless natural and cultural attractions that have allowed its cantons to develop projects to increase the influx of tourists to them. . The Loja canton, especially its rural parishes, are worthy representatives who possess great cultural and natural wealth. Bearing in mind that each of the rural parishes of the Loja canton possess great tourist potential, it was important to develop the present research work, for which purpose it was proposed as a general objective: "To elaborate a proposal for the Agrotourism route of the parishes Vilcabamba, Yangana and Quinara of the Loja canton, Loja Province "within this objective it includes everything related to the development of the research work, to achieve it, two specific objectives were proposed; "Carry out the tourist diagnosis of the Vilcabamba, Yangana and Quinara parishes of the Loja Canton, Loja Province". For this purpose, the Analytical Method was used to analyze the tourist attractions of the Vilcabamba, Yangana and Quinara parishes, which they are part of the object of study; the Inductive Method, which was used to analyze the particularities of the parishes and communities in economic and sociocultural aspects; thus, the techniques of direct observation and interview were applied; In addition, the Carla Ricaurte Quijano Diagnostic Matrix, MINTUR Tourist Inventory Sheets and Summary Sheets. The support of the Land Management Plan served as a complement for the collection of information: geographic, tourist, economic, political and social; finally the SWOT matrix was made to determine the current situation of the canton. The second objective was also proposed: "Propose the design of the Agrotourism Route for the Vilcabamba, Yangana and Quinara parishes of the Canton of Loja." For this purpose, the Synthetic Method was used to determine which communities will be integrated into the tourism activity, taking in account the potential that they possess, in addition, the use of the Global Positioning System (GPS) was used to carry out the survey of the geographical coordinates of the tourist attractions, as well as the signage to be used in addition to times and distances between them ; photographic camera that was used as digital support, and the matrix to validate tourist routes, designed by the Ministry of Tourism; In addition, pictograms of the 5 attractions, activities and tourist services were used for the design and preparation of the route map, in addition an identification mark was created using the main elements that stand out within it, finally the name of the Agrotouristic Route was established Tierras de Riqueza, complemented with the elaboration of the script and itinerary following the established order of the same, strategies were also developed for the promotion and diffusion of the route, the first strategy consists of the preparation of advertising media such as: triptychs; souvenirs such as: t-shirt, caps, spheres; Finally, the proposal was socialized, using the technique of the Rapid Analysis Method and Participatory Planning (MARPP), which consists of three phases; the first is the call made through an office addressed to the presidents of the parochial GADs of Vilcabamba, Yangana and Quinara, Dr. Diego Guerrero, Lic. Max Samaniego and Mr. Lenin Cuenca respectively, requesting date for socialization; In the second phase, the results of the research work obtained on the development of the Land Route of Wealth were presented finally in the third phase the observations were raised. The result of the socialization determined that the Route "Agroturística Tierras de Riqueza" will contribute to the promotion of agricultural activity as a new tourist alternative for each of the parishes. Finally, the conclusions and recommendations of the thesis work were presented, which are mostly addressed to the Decentralized Autonomous Governments of the parishes in question and to the agricultural producers of each of them, considered on the route; where it was established that the parishes have large agricultural and livestock production that can be used for the creation of new tourism alternatives, which could be stimulated by parish GADs through training to benefit their crops and quality of tourism services.